ANALISIS PERSETUJUAN TERHADAP SUATU PEKERJAAN PASCA BELAKUNYA UU CIPTA KERJA - Arofah, Laila; Jumhana, Enjum; Febriyant, Afi Nurul; Hidayah, Jihan; Wahyu, Muhammad (Yayasan Education and Social Center, 2025)
Fixed Term To Employment Agreement (PKWT) is one form of employment relationship that is needed and has been regulated in the legislation. This change covers aspects of work duration, compensation arrangements, contract flexibility, and labor protection. The existence of legislation on Job Creation makes it easier for companies to use PKWT, including more flexible contract extensions. However, on the other hand, and there are concerns that this new regulation could reduce job stability and guarantees of rights for the workers, especially in terms of the social security, and end-of-contract compensation, and protection against termination of employment. The new regulation also poses challenges in implementation, especially in ensuring company compliance with compensation obligations and avoiding potential abuse.